Decentralised application for crowdfunding using blockchain technology. (7th September 2021) - Gururaj, H.L.; Janhavi, V.; Holla, Abhishek M.; Kumar, Ashwin A.; Bhumika, R.; Goundar, Sam
Crowdfunding is a way for people, businesses, and charities to raise money. It works through individuals or organisations who invest in (or donate to) crowdfunding projects in return for a potential profit or reward. Investing this way can be risky. Security is the main challenging issue in crowdfunding contracts. Using existing literature on crowdfunding and blockchain technology, they put forward a conceptual framework that can provide the solution to the problems related to crowdfunding contracts using blockchain technology. This methodology points out the potential of crowdfunding decentralised applications to lower market inefficiencies by bypassing third parties and easing trades on secondary markets. This platform eliminates the interference of the middlemen. It is highly transparent and secure. A decentralised approach to crowdfunding forfeits all fees for the investor. It also gives a share of the project to the receiver. This model establishes a flexible platform for the fundraiser to start a campaign. The funders invest the amount if they feel the project to be genuine. Once 50% of the funds are received, it will be transferred to the initiator. It establishes a peer-to-peer relationship between the investor and the receiver.